Physicochemical and sensory evaluation of wine brandies aged using oak and chestnut wood simultaneously in wooden barrels and in stainless steel tanks with staves - Canas, S. (2017)
Submitted by Maria Silva (mfsilva@ipcb.pt) on 2017-05-30T10:57:12Z No. of bitstreams: 1 2016_Canas_et_al-2016-International_Journal_of_Food_Science_&_Technology.pdf: 240618 bytes, checksum: 2a50bd3b35ba6a8ce8a0c19154203bcb (MD5)